Diagnóstico serológico de la hepatitis b - Macas Silva, Daysi Patricia (Machala : Universidad Técnica de Machala, 2019)
Introduction: The Hepatitis B virus is a common pathogen that chronically infects and leads to complications such as cirrhosis, hepatocellular carcinoma and liver cancer. The fact of being very prevalent worldwide highlights its importance in the detection of its definitive diagnosis through the results of serological tests. The present publication was aimed at analyzing updated data on replication markers as a diagnostic method of Hepatitis B for a greater understanding of the disease and its different treatments. Development: 10 articles indexed from the last 5 years obtained through biomedical research search engines such as PubMed, Google Scholar, The New England Journal of Medicine, Medscape and ScienceDirect; including a clinical practice guide of the World Gastroenterology Organization, in which epidemiological data, clinical characteristics and innovation in the diagnosis, treatment and prevention of HBV were investigated. Conclusions: From the analyzed studies, it reveals various diagnostic findings after the arrest of the serological markers of the Hepatitis B virus, which concludes with greater clinical significance the HBsAg, HBcAg, HBeAg and its antibodies as the anti-HBs, the anti-core. , anti-core IG M, total anti core and the anti e; Its usefulness for the differentiation between an acute infection of a chronic infection was demonstrated, allowing later the realization of a greater vigilance in the epidemiological order and in the therapeutic behaviors to be executed.
Introducción: El virus de la Hepatitis B es un patógeno común que infecta de forma crónica y conlleva a complicaciones como cirrosis, carcinoma hepatocelular y cáncer hepático. El hecho de ser muy prevalente a nivel mundial demarca su importancia en la detección de su diagnóstico definitivo mediante los resultados de pruebas serológicas. La presente publicación se planteó con el objetivo de analizar datos actualizados sobre los marcadores de replicación como método diagnóstico de la Hepatitis B para una mayor compresión de la enfermedad y sus diferentes tratamientos. Desarrollo: Se seleccionaron 10 artículos indexados de los últimos 5 años obtenida a través de motores de búsqueda de investigación biomédica como PubMed, Google Académico, The New England Journal of Medicine, Medscape y ScienceDirect; incluyendo una guía de práctica clínica de la Organización Mundial de Gastroenterología, en los cuales se investigó sobre datos epidemiológicos, características clínicas e innovación en el diagnóstico, tratamiento y prevención sobre el VHB. Conclusiones: De los estudios analizados revela diversos hallazgos diagnósticos tras la detención de los marcadores serológicos del virus de Hepatitis B los cuales se concluye con mayor significancia clínica la detención del HBsAg, HBcAg, HBeAg y sus anticuerpos como el anti-HBs, el anti core, anti core IG M, anti core total y el anti e; se demostró su utilidad para la diferenciación entre una infección aguda de una infección crónica permitiendo posteriormente la realización de una mayor vigilancia en el orden epidemiológico y en las conductas terapéuticas a ejecutarse.
Keywords: HEPATITIS; HBSAG; HBEAG; MARCADORES SEROLOGICOS